Covalent immobilization of Candida rugosa lipase at alkaline pH and their application in the regioselective deprotection of per-O-acetylated thymidine - Rivero, Cintia Wanda (2016)
Lipase from Candida rugosa (CRL) was stabilized at alkaline pH to overcome the inactivation problem and was immobilized for the first time by multipoint covalent attachment on different aldehyde-activated matrices. PEG was used as a stabilizing agent on the activity of CRL. At these conditions, CRL maintained 50% activity at pH 10 after 17 h incubation in the presence of 40% (w/v) of PEG, whereas the enzyme without additive was instantaneously inactive after incubation at pH 10. Thus, this enzyme was covalently immobilized at alkaline pH on three aldehyde-activated supports: aldehyde-activated Sepharose, aldehyde-activated Lewatit105 and heterofunctional aldehyde-activated EDA-Sepharose in high overall yields. Heterogeneous stable CRL catalysts at high temperature and solvent were obtained. The aldehyde-activated Sepharose-CRL preparation maintained 70% activity at 50 °C or 30% (v/v) acetonitrile after 22 h and exhibited high regioselectivity in the deprotection process of per-O-acetylated thymidine, producing the 3ʹ-OH-5ʹ-OAc-thymidine in 91% yield at pH 5.